INNOVATIVE METHODS IN TEACHING APHORISMS USING ARTIFICIAL INTELLIGENCE - ASHUROVA, Feruza Lutpullayevna (The Lingua Spectrum, 2025)
Aphorisms, as condensed forms of cultural and philosophical wisdom, serve as valuable linguistic, cognitive, and communicative tools in language education. In the era of artificial intelligence (AI), traditional approaches to teaching aphorisms are expanding into new pedagogical possibilities supported by digital technologies. This paper examines innovative methods for teaching aphorisms in foreign-language classrooms, with a particular emphasis on AI-assisted learning. The study highlights how AI can personalize instruction, generate creative tasks, support multilingual interpretation, and enhance students’ critical thinking and cultural awareness. The findings demonstrate that integrating AI transforms aphorism teaching from passive memorization into an interactive, creative, and cognitively rich experience.